Nanowire solar cells: Electro-optical performance - Witzigmann, Bernd (Handbook of Optoelectronic Device Modeling and Simulation: Lasers, Modulators, Photodetectors, Solar Cells, and Numerical Methods, 2017)
Nanowire arrays show unique optical and electronic features for photovoltaic applications. It has been demonstrated that they exhibit intrinsic optical antireflection properties [1, 2]. Moreover, they also can act as optical microconcentrators [3] that focus light to an active region. Nanowires have a large aspect ratio, improving the electronic properties by combining a long optical absorption path along the wire axis and a short lateral carrier extraction [4]. Short carrier extraction paths are beneficial for the carrier collection efficiency. These mechanisms are illustrated in Figure 42.1. On the left, a conventional bulk solar cell collects light in the vertical direction, and the photogenerated carriers move to the respective contacts causing the photo current. A nanostructured solar cell (Figure 42.1a) can act as an optical concentrator in order to focus the incoming light to a small area. Moreover, the carrier extraction path length to the contacts is reduced, which minimizes the probability of carrier loss by unwanted recombination.
CRIS-Team Scopus Importer:2021-06-11